PENGEMBANGAN MEDIA BELAJAR LITERASI DIGITAL BERBASIS GAME EDUKASI DALAM MENINGKATKAN MINAT BACA KELAS 2 SD - Meilisa; Azmi Alwi, Nur (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to develop digital literacy learning media based on educational games to increase reading interest in grade 2 elementary school students. This media was designed using the Constructs 2 application, by integrating Strengthening Character Education (PPK) values ​​such as religious, nationalist, independent, integrity and mutual cooperation. The development process follows a research and development model that produces valid, innovative, flexible and efficient products. This educational game is designed to maximize student interaction with learning through a fun, interactive and meaningful learning experience. The research results show that this learning media is able to increase students' interest in reading as well as train superior characters that are relevant to the demands of the era of globalization.